(untitled) (Itinerarios Educativos, 2022)
This article analyzes a set of transformations here called the crisis of the principle of selectivity with unequal integration in secondary school. From a historical perspective, the founding features of secondary school are: selectivity, encyclopedism, and its weakening since the mid–20th century. We also discuss the convergence of new social sectors that gained access to secondary school, the recognition of education as a right, and the changes in curricula, teaching perspectives and school work organization. This enables criticism of secondary school to be inscribed —according to school performance, overage attendance, grade repetition, and graduation rates— in dynamic processes that hold, reconfigure and give birth to new educational inequalities. Finally, we provide interpretations on some tensions in schooling processes, focusing on the emergence of new schooling modalities that, contrarily to their intention, tend to fragment the pedagogical dimension of the secondary level. These structural and pedagogical key aspects gain relevance in the current return to full face–to–face attendance, since even with greater educational investments and improved socioeconomic and schooling conditions, the main challenge remains pedagogical.